Preperitoneal pelvic balloon tamponade—an effective intervention to control pelvic injury hemorrhage in a swine model - Jin, Xiaogao; Chu, Qinjun; Bing, Hailong; Li, Fang; Bai, Jingyue; Lou, Junge; Sun, Liwei; Zhang, Chenxi; Lin, Lin; Li, Liumei; Wang, Haibo; Zhou, Zhanfeng; et al. (Frontiers in Bioengineering and Biotechnology, 2024)
This study aimed to estimate the effects of the volume of preperitoneal balloon (PPB) on arterial and venous hemorrhage in a swine pelvic fracture model.Twenty-four swine were randomized into 0-ml, 500-ml, 800-ml, and 1000-ml intrahematoma PPB groups. They were subjected to open-book pelvic fracture and reproducible injuries in the external iliac artery and vein. The pelvic binder and IH-PPBs with different volumes of fluid were applied to control the active hemorrhage after arterial and venous injuries. The survival time and rate during 60-minute observation and digital subtraction angiography (DSA) images were the primary endpoints in this study. Secondary endpoints included survival rate within 70 min, peritoneal pressure, hemodynamics, blood loss, infusion fluid, blood pH, and lactate concentration.Our results indicated that the 800-ml and 1000-ml groups had a higher survival rate (0%, 50%, 100% and 100% for 0, 500, 800, and 1000-ml groups respectively; p<0.0001)and longer survival time (13.83±2.64, 24.50±6.29, 55.00±6.33, and 60.00±0.00 min for 0, 500, 800, and 1000 groups respectively; p<0.0005) than the 0-ml or 500-ml groups during the 60 min observation. Contrastingly, survival rate and time were comparable between 800ml and 1000-ml groups during the 60-minute observation. The IH-PPB volume was associated with an increase in the pressure of the balloon and the preperitoneal pressure but had no effect on the bladder pressure. Lastly, the 1000-ml group had a higher mean arterial pressure and systemic vascular resistance than the 800-ml group.IH-PPB volume-dependently controls vascular bleeding after pelvic fracture in the swine model. IH-PPB with a volume of 800ml and 1000ml efficiently managed pelvic fractureassociated arterial and venous hemorrhage and enhanced survival time and rate in the swine model without evidences of visceral injury.